Characterization of dust accumulated on photovoltaic panels in Doha, Qatar. (15th January 2017) - Javed, Wasim; Wubulikasimu, Yiming; Figgis, Benjamin; Guo, Bing
Highlights: Dust accumulation rate and particle size both decrease as exposure time increases. PV performance loss due to unit amount of dust loading is dependent on the season. Dust consists primarily limestone and dolomite, with quartz as a minor component. Accumulated dust particles agglomerate as exposure time increases. Abstract: In this study, samples of dust naturally accumulated for various exposure times on photovoltaic (PV) panels were collected and characterized over a period of ten months in a solar test facility located in Doha, Qatar. The dust accumulation rate (DAR) over the exposure time was determined gravimetrically. The dust samples were characterized using particle size analysis, X-ray fluorescence (XRF), X-ray diffraction (XRD), and scanning electron microscopy (SEM). The cleanness index change rate (CICR), a measure of how fast the PV power output degrades due to soiling, was found to have strong negative correlation with DAR, but the CICR/DAR ratio was found to differ between winter and summer. The DAR and the mean particle size of the accumulated dust both decreased with increasing exposure time, reaching relatively steady values for longer exposure times. Calcium was found to be the most abundant element in the accumulated dust, followed by silicon, iron, magnesium and aluminum. Calcite, dolomite, and quartz were the dominant minerals in the accumulated dust, with gypsum being a minor component. Dust collected after dust-storm events had higher proportions of halite and quartz contents than non-dust-storm days, depending on the direction of the wind. Also, dust particles accumulated on PV panels appeared to agglomerate as the exposure time increased. The data provided in this paper will be useful for quantitatively determine the degree of soiling and its effect on PV performance in Qatar and regions with similar environmental conditions. The data will also be useful for the selection of soiling mitigation technologies.